2014
DOI: 10.4081/ejh.2014.2387
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of local renin-angiotensin system components in chondrocytes

Abstract: In 2013, we reported that local reninangiotensin system (local RAS) components express during the hypertrophic differentiation of chondrocytes and can modulate it, using ATDC5 cell line that involves differentiation from mesenchymal stem cells to calcified hypertrophic chondrocytes. However, the expressions of local RAS components in normal chondrocytes have not been revealed yet. The purpose of this study is to examine the expression of the local RAS components in chondrocytes in vivo and the conditions allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 15 publications
0
32
0
Order By: Relevance
“…OA represents a major clinical and scientific challenge for clinicians and biologists due to the limited repair capacity of articular cartilage, which is rich in matrix proteins but also avascular [61]. Articular cartilage defects cause pain, reduced joint function, and significant disability [62].…”
Section: Chit1 and Dmmentioning
confidence: 99%
“…OA represents a major clinical and scientific challenge for clinicians and biologists due to the limited repair capacity of articular cartilage, which is rich in matrix proteins but also avascular [61]. Articular cartilage defects cause pain, reduced joint function, and significant disability [62].…”
Section: Chit1 and Dmmentioning
confidence: 99%
“…The angiotensin II (Ang II) type 1 receptor (AT1R) has been reported to be expressed in hypertrophic chondrocytes of human articular cartilage . In vitro , local RAS components are expressed in cultured chondrocytes and are involved in modulation of chondrocyte hypertrophic differentiation . Taken together, these findings suggest that the local RAS components in chondrocytes may be involved in cartilage degeneration through the hypertrophic differentiation of chondrocytes.…”
mentioning
confidence: 99%
“…On the other hand, it was already reported that Ang II induces inflammation and that Ang II activates, via AT1R, NF-κB 43,54,55 which regulates expression of various genes related to inflammation. Furthermore, inflammation by stimulation of IL-1β or tumor necrosis factor-α enhances the expressions of AT1R, 14 and inflammation by mechanical stress in OA activates AT1R. 50,51 Considering these findings, contribution of Ang II-induced inflammation to differentiation of chondrocytes is strongly suggested although it is still unclear how inflammation promotes differentiation of chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…11 However, the effects of Ang II on chondrocytes and cartilage metabolism are still unclear, although Ang II receptors were shown to be expressed in cultured chondrocytes 12,13 and chondrocytes in vivo. 14 Some papers reported a beneficial effect of an angiotensin converting enzyme inhibitor (ACEI) or an Ang II receptor blocker (ARB) on fracture healing 15,16 in basic experiments, suggesting involvement of RAS in chondral metabolism. However, the direct effects of Ang II itself via Ang II receptors on differentiation, proliferation and apoptosis of chondrocytes, especially in vivo, are not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%